Manajemen kearsipan: Sistem pemberkasan arsip aktif di Biro Persidangan 1 Sekretariat Jenderal DPR RI - Ardiyanti, Karina Elsa (Maliki Interdisciplinary Journal, 2024)
The development of science and information technology in the current era of globalization has a major influence in all fields, especially for an organization, both government and non-government institutions. Archives as an important source of information can support the process of administrative and bureaucratic activities. Session Bureau 1 which has the task of filing active archives at the Secretariat General of the DPR RI. The active archival filing system at the Trial Bureau 1 uses the subject system and the filing process manually. The aims of this study were (1) to find out the implementation of active archival filing used at Session Bureau 1 of the DPR RI Secretariat General, and (2) to find out the obstacles encountered when filing active archives at Session Bureau 1 of the DPR RI Secretariat General. This research method uses a qualitative research approach with data collection techniques, interviews, participant observation and document study. The results of this study are as follows: (1) The active archive filing system at the Session Bureau 1 of the Secretariat General of the DPR RI starts from the stages of checking, indexing, assigning classification codes, giving cross points, labeling, compiling lists of active archives to storing active archives. The need for facilities and infrastructure in supporting active archival filing activities within the Bureau of Trial I is also complete and in accordance with the guidelines; (2) Constraints faced with the frequent accumulation of active archives due to archive checks that are not carried out routinely, and the use of labels that are still written in pencil so that the labeling process does not look neat. Meanwhile, there is a lack of understanding of the technical use of cross pointing because the filing is not carried out by archivists but by administrative staff so that archival files have not been fully implemented in the filing process.